Portable nanopore-sequencing technology: Trends in development and applications - Chen, Pin; Sun, Zepeng; Wang, Jiawei; Liu, Xinlong; Bai, Yun; Chen, Jiang; Liu, Anna; Qiao, Feng; Chen, Yang; Yuan, Chenyan; Sha, Jingjie; Zhang, Jinghui; et al. (Frontiers in Microbiology, 2023)
Sequencing technology is the most commonly used technology in molecular biology research and an essential pillar for the development and applications of molecular biology. Since 1977, when the first generation of sequencing technology opened the door to interpreting the genetic code, sequencing technology has been developing for four generations. It has applications in all aspects of life and scientific research, such as disease diagnosis, drug target discovery, pathological research, species protection, and SARS-CoV-2 detection. However, the first- and second-generation sequencing technology relied on fluorescence detection systems and DNA polymerization enzyme systems, which increased the cost of sequencing technology and limited the scope of applications of sequencing technology. The third generation sequencing technology performs a PCR-free and single molecule sequencing, however, it still depends on fluorescence detection device To break through these limitations, researchers have made arduous efforts to develop a new generation of portable sequencing technology represented by nanopore sequencing. Nanopore technology has the advantages of small size and convenient portability, independent of biochemical reagents, and direct reading using physical methods. This paper reviews the research and development process of nanopore sequencing technology from the laboratory to commercially viable tools; discusses the main types of nanopore sequencing technologies and their various applications in solving a wide range of real-world problems. In addition, the paper collates the analysis tools necessary for performing different processing tasks in nanopore sequencing. Finally, we highlight the challenges of nanopore sequencing technology and its future research and application directions